Tissue Reactive Hyperplastic Lesions of Oral Mucosa: A 10 Years Retrospective Study and Literature Review - Bhatnagar, Shruti; Swati, Mutyala; Agrawal, Nikita; Bongirwar, Shivani; Kumar, Prabhat; Chandra, Avinash (Journal of Neonatal Surgery, 2025)
Objective: Tissue Reactive hyperplastic lesions (TRHL) are reactions to local injury of the oral mucous membrane. The cause varies from mechanical injury to hormonal imbalance. Since they closely resemble each other in clinical as well as histological picture thus confusing the examiner all the more. Materials and Method: The four commonly found reactive lesions are Focal fibrous hyperplasia (FFH), Pyogenic granuloma (PG), Peripheral ossifying fibroma (POF), Peripheral giant cell granuloma (PGCG). The present study reviewed 238 cases, over a period of 10 years focussed on these four lesions. The clinical and histopathological records were assessed and documented. Any incomplete record was discarded. The records were categorised based on prevalence of jaw distribution, age, size and gender. Statistical analysis was done using chi square test and corelation was assessed using Pearsons’s chi square ratio. Results: The fibrous hyperplastic lesion was most prevalent lesion followed by Pyogenic granuloma, Peripheral ossifying fibroma and least was Peripheral giant cell granuloma. The most common site is buccal mucosa and gingiva. The age group which is most susceptible is from 3rd decade to 5th decade. Conclusion: The lesions are difficult to identify and recurrence rate often leaves the patient and operator troubled. Hence thorough knowledge and understanding of cause and manifestation in particular is warranted for proper diagnosis and treatment.